In vitro Assessment of Solar Filters for Erythropoietic Protoporphyria in the Action Spectrum of Protoporphyrin IX - Sernicola, Alvise; Cama, Elena; Pelizzo, Maria Guglielmina; Tessarolo, Enrico; Nicolli, Annamaria; Viero, Giulia; Alaibac, Mauro (Frontiers in Medicine, 2021)
Introduction: Subjects with erythropoietic protoporphyria rely on broad-spectrum sunscreens with high sun protection factor, which is not informative on efficacy in the absorption spectrum of protoporphyrin IX, spanning visible radiation and peaking around 408 nm. Photoactivation of protoporphyrin IX is responsible for painful skin photosensitivity in erythropoietic protoporphyria. The authors assessed the protective efficacy of six sunscreens in vitro in the absorption spectrum of protoporphyrin IX. Method: Transmittance measurements were performed in the 300-850 nm wavelengths on samples of six photoprotective products applied to polymethyl methacrylate plates. Porphyrin protection factor was calculated in the 300-700 nm region to provide a measurement for the efficacy of each product based on the action spectrum of protoporphyrin IX. Results: Product A showed the highest porphyrin protection factor among tested products with a median value of 4,22. Product A is a sunscreen containing organic filters, titanium dioxide and synthetic iron oxides, pigmentary grade active ingredients that absorb visible radiation. Other products showed inefficient protection in the visible, with transmittance between 75 and 95% at 500 nm. The low porphyrin protection factor of inorganic filter product B was attributed to particle micronization, as declared by the manufacturer. Conclusion: Adding porphyrin protection factor to sunscreen labeling could help patients with erythropoietic protoporphyria and other photosensitivity disorders identify products tailored on their specific needs. The development of sunscreens providing protection from visible radiation and excellent cosmetical tolerability could improve the lifestyle of patients with erythropoietic protoporphyria.